Music as a manifestation of life: exploring enactivism and the ‘eastern perspective’ for music education - van der Schyff, Dylan (Frontiers in Psychology, 2015)
The enactive approach to cognition is developed in the context of music and music education. I discuss how this embodied point of view affords a relational and bio-cultural perspective on music that decentres the Western focus on language, symbol and representation as the fundamental arbiters of meaning. I then explore how this ‘life-based’ approach to cognition and meaning-making offers a welcome alternative to standard Western academic approaches to music education. More specifically, I consider how the enactive perspective may aid in developing deeper ecological understandings of the transformative, extended and interpenetrative nature of the embodied musical mind; and thus help (re)connect students and teachers to the lived experience of their own learning and teaching. Following this, I examine related concepts associated with Buddhist psychology in order to develop possibilities for a contemplative music pedagogy. To conclude, I consider how an enactive-contemplative perspective may help students and teachers awaken to the possibilities of music education as ‘ontological education.’ That is, through a deeper understanding of ‘music as a manifestation of life’ rediscover their primordial nature as autopoietic and world-making creatures and thus engage more deeply with musicality as a means of forming richer and more compassionate relationships with their peers, their communities and the ‘natural’ and cultural worlds they inhabit.